2009
DOI: 10.1143/jjap.48.110202
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Magnesium-Incorporated Semipolar GaN(10\bar1\bar1) Surfaces

Abstract: The stability of Mg-incorporated GaN surfaces with semipolar ( 101 1 1 1) orientation is investigated by performing first-principles pseudopotential calculations. Several Mg-incorporated surfaces, in which a single Mg atom is substituted for the topmost Ga atom, can be formed when the surfaces include step edges in the [0 1 100] direction. This implies that on the stepped surfaces Mg atoms can be easily incorporated into electrically active substitutional lattice sites, leading to high hole concentrations. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(107 citation statements)
references
References 23 publications
3
104
0
Order By: Relevance
“…A thermodynamic approach that includes chemical potentials that are appropriate for realistic growth conditions has revealed that hydrogen stabilizes Mg-rich surface reconstructions for both GaN(0001) and false(1true1¯00false) surfaces [135]. In addition, the stability of the Mg-incorporated GaNfalse(1true1¯0true1¯false) surface has been examined [40] to explain high hole concentrations in the Mg-doped semipolar GaNfalse(1true1¯0true1¯false) surface [136]. …”
Section: Applications To Iii-nitride Surfacesmentioning
confidence: 99%
“…A thermodynamic approach that includes chemical potentials that are appropriate for realistic growth conditions has revealed that hydrogen stabilizes Mg-rich surface reconstructions for both GaN(0001) and false(1true1¯00false) surfaces [135]. In addition, the stability of the Mg-incorporated GaNfalse(1true1¯0true1¯false) surface has been examined [40] to explain high hole concentrations in the Mg-doped semipolar GaNfalse(1true1¯0true1¯false) surface [136]. …”
Section: Applications To Iii-nitride Surfacesmentioning
confidence: 99%
“…The power of this approach is not only on understanding the epitaxial growth processes but also on producing fundamental data such as surface phase diagrams as functions of growth conditions. Surface phase diagrams and elemental growth processes have been extensively investigated using similar approach for various semiconductors except InAs and InP such as GaAs [18,41,[103][104][105][106][107][108] and III-Nirides [7][8][9][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128]. Figure 36 summarizes the calculated surface phase diagrams with different orientations for AlN and GaN under H-rich conditions during MOVPE growth.…”
Section: Discussionmentioning
confidence: 99%
“…I I is written as 11.9) where m I is the reduced mass and r is the radius of gyration. The detailed procedure in the total energy calculations has been reported elsewhere [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. In the total energy calculations for the compound semiconductor surfaces with various atomic arrangements, we used the ab initio pseudopotential method based on the local-density functional formalism [9] within the generalized gradient approximation [10].…”
Section: Chemical Potentialmentioning
confidence: 99%
“…Generally, blue light-emitting diodes (LEDs) and laser diodes (LDs) using III-nitrides are fabricated on the (0001)-polar surface. Since the demonstration of InGaN/GaN LEDs on semipolar (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) bulk GaN [94,95], the (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) plane has been the most promising among the semipolar orientations. This is because there are large internal piezoelectric fields in the III-nitride layers grown on the (0001) heterosubstrates.…”
Section: Ganmentioning
confidence: 99%
See 1 more Smart Citation